Qualitative characterization of healthcare wastes - Noman, Efaq; Al-Gheethi, Adel; A. Talip, Balkis; Radin Mohamed, Radin Maya Saphira (Springer Nature, 2020)
The biological hazard inherent in the clinical wastes should be considered during the management and treatment process as well as the disposal into the environment. In this chapter, the risks associated with the clinical wastes as well as the management of these wastes are discussed. The chapter focused on reviewing the types of healthcare wastes generated from hospitals and clinics as well as the regulations and management practices used for these wastes. Moreover, the health risk associated with the infectious agents which have the potential to be transmitted into the environment. It has appeared that the clinical wastes represent real hazards for the human health and the environment if they were not managed properly.